TANGGUNG JAWAB ATAS PENYALAHGUNAAN KEADAAN DALAM PEMBUATAN AKTA PERJANJIAN PENGIKATAN JUAL BELI YANG DIBUAT OLEH NOTARIS ATAS PERMINTAAN PARA PIHAK DAN AKIBAT HUKUMNYA - Stefanus Dikchney Soleman; Irhamsyah, Irhamsyah; Refki Ridwan (Bajang Institute, 2025)
In the scientific field of notary law, especially legal agreements, almost some Notaries become involved in the court due to the abuse of circumstances when making an agreement based on an authentic deed at the will of the parties who come to the Notary. The abuse of the situation in question arises as a result of an unbalanced relationship between the parties, as one of which is the abuse of the state of the Notary deed in the Community, the existence of a sale and purchase binding agreement (PPJB) and other Notary deeds made on the basis of debts and receivables. As for the formulation of the problem in this study, what are the legal consequences and legal liability for the abuse of the existence of the deed of binding sale and purchase agreement made by the Notary at the will of the parties? The theories used in this study are the theory of legal consequences of R. Soeroso and the theory of legal responsibility of Hans Kelsen.The method used in this study is a type of normative juridical research, namely literature law research or secondary data with sources of primary, secondary and tertiary legal materials. The research approach used is a legislative, conceptual, case, and analytical approach as well as a technique for collecting legal materials by identifying and inventorying positive legal rules, literature, books, journals, and other sources of legal materials. For legal material analysis techniques, it is carried out by grammatical and systematic legal interpretation as well as legal construction methods.As a result of the Abuse of the Condition of the Sale and Purchase Agreement Deed made by the Notary at the Desire of the Parties, the aggrieved parties can apply for the cancellation of the PPJB deed made by the Notary at the will of the parties and Legal Liability for the Abuse of the Condition of the PPJB Deed made by the Notary at the will of the Notary Parties can be asked for responsibility in the form of administrative liability, and civil liability